Assessing the Association of Cooking Fuel Type on chronic respiratory diseases among middle-aged and older adults in China: Insights from residential area and self-care capability - Junzhou Xu; Ling Zhang (Preventive Medicine Reports)
Objective: This study aimed to evaluate the association between clean versus solid cooking fuels and chronic respiratory diseases (CRD) in adults aged 45 and older, focusing on the moderating effects of urban-rural location and self-care ability (independent, partially independent, or dependent). Methods: Using cross-sectional data from the 2020 China Health and Retirement Longitudinal Study, logistic regression was applied to examine the relationship between cooking fuel types and CRD, while exploring the moderating effects of residential area and self-care ability. Robustness checks were conducted to confirm the findings. Results: The use of clean cooking fuels was linked to lower CRD prevalence across all groups. While urban residents had a higher baseline CRD risk, the relationship between clean fuels and CRD was similar in both urban and rural areas. Individuals with poorer self-care abilities had a higher CRD risk, regardless of fuel type, indicating that clean fuels alone may not fully mitigate health risks for this group. Conclusions: Clean cooking fuels are linked to lower CRD prevalence in both urban and rural populations, and their protective effect is similar across these groups. Poorer self-care ability is associated with higher CRD risk, highlighting that interventions beyond fuel switching are necessary for vulnerable individuals with limited self-care abilities. These findings underscore the need for comprehensive public health strategies.